2020
DOI: 10.1111/jvim.15799
|View full text |Cite
|
Sign up to set email alerts
|

Brain proton magnetic resonance spectroscopy findings in a Beagle dog with genetically confirmed Lafora disease

Abstract: Cortical atrophy has been identified using magnetic resonance imaging (MRI) in humans and dogs with Lafora disease (LD). In humans, proton magnetic resonance spectroscopy (1HMRS) of the brain indicates decreased N ‐acetyl‐aspartate (NAA) relative to other brain metabolites. Brain 1HMRS findings in dogs with LD are lacking. A 6‐year‐old female Beagle was presented with a history of a single generalized tonic‐clonic seizure and episodic reflex myoclonus. Clinical, hematological, and neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…The onset of clinical signs at a median of 8.3 years developed relatively late considering a disease caused by an underlying genetic defect. In the literature, single case reports describe a similar age of onset of 6 to 9 years in 7 Beagles 13,14,20,24,26 . French bulldogs with Lafora disease seem to be affected at a similar age of 7 to 9 years, whereas Miniature Wirehaired Dachshunds develop clinical signs slightly earlier with an average age of 6.9 years (range, 3.5‐12.0) 12,16,17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The onset of clinical signs at a median of 8.3 years developed relatively late considering a disease caused by an underlying genetic defect. In the literature, single case reports describe a similar age of onset of 6 to 9 years in 7 Beagles 13,14,20,24,26 . French bulldogs with Lafora disease seem to be affected at a similar age of 7 to 9 years, whereas Miniature Wirehaired Dachshunds develop clinical signs slightly earlier with an average age of 6.9 years (range, 3.5‐12.0) 12,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Miniature dachshunds a defect of a the 12‐nucleotide repeat sequence that is unique to the canine NHLRC1 (EPM2B) gene has been identified in this breed 20 . Common clinical signs include spontaneous and myoclonic events triggered by noises or visual stimuli, hypnic myoclonus as well as generalized tonic‐clonic seizures, which usually develop in dogs at an age of 6 to 9 years 13,14,20,22,24,26 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, other studies have reported certain levels of brain atrophy in patients with Lafora disease at different stages of the disease. Diffuse cortical [ 16 , 17 ], cerebellar [ 18 ], cerebral [ 19 , 20 ] or both, cerebellar and cerebral [ 21 , 22 , 23 ] atrophy were observed in certain patients, mainly in more advanced stages of the disease [ 15 ]. However, with 2-deoxy-2-[18F]fluoro- D -glucose (FDG)–positron emission tomography (PET), a diffuse decrease in cortical [ 24 ] or cerebral [ 25 ] glucose metabolism has been reported in several patients, especially in posterior areas, such as the cerebellum [ 26 , 27 ] and occipital lobes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a significant reduction in the NAA/Cho ratio in the cerebellum was found in a series of 12 patients with Lafora disease, along with an association between metabolite alterations and some clinical parameters (myoclonus and ataxia) [31]. Recently, an in vivo study of 1 [H] MRS study in the thalamus of a Beagle dog showed a decrease in molar concentrations of glutamate + glutamine (Glu+Gln), NAA and mIns + glycine (mIns+Gly) and higher concentrations of total Cho (tCho) and phosphoethanolamine (PE) [23].…”
Section: Introductionmentioning
confidence: 99%